Impact of ovotransferrin on the membrane integrity of Salmonella Enteritidis under egg-white conditions - Legros, Julie; Bonnassie, Sylvie; Cochet, Marie-Françoise; Jan, Sophie; Andrews, Simon C.; Baron, Florence (Frontiers in Microbiology, 2025)
IntroductionEggs can mediate foodborne disease resulting in salmonellosis outbreaks that are most commonly caused by Salmonella enterica serovar Enteritidis. Ovotransferrin is a prominent egg-white antimicrobial glycoprotein belonging to the transferrin family, members of which exhibit powerful iron-chelating activity. However, several studies have also described the ability of transferrin proteins to disrupt bacterial membranes. This study aimed to investigate the antimicrobial activity of ovotransferrin toward S. Enteritidis membranes at 30°C under egg-white conditions.Materials and methodsThis aim was supported by the deployment of a synthetic medium designed to mimic egg-white (matching the ionic composition and pH). The ability of ovotransferrin to induce bacterial membrane permeabilization in S. Enteritidis was investigated by measuring substrate accessibility to periplasmic β-lactamase and cytosolic β-galactosidase.ResultsThe depolarization of the inner membrane of S. Enteritidis was measured using a fluorescence probe [DiSC3(5)]. The results show that ovotransferrin induces permeabilization of the outer membrane but not the inner membrane whereas egg white permeabilizes both membranes. In addition, the dissipation of the proton motive force by egg white was found to involve a contribution by ovotransferrin since this protein provoked inner-membrane depolarization.DiscussionIt can thus be concluded that ovotransferrin exerts a membranes perturbation activity on S. Enteritidis under egg-white conditions, in addition to its well-known iron-chelation activity.